Enhancing The Professionalism Of Vocational High School Teacher Candidates Through The Reflective Learning Model Based On The Unity Of Sciences - I Gede Budi Mahendra; Viverdy Memah; Billy Killis; Jocke Jonathan Rapar (Journal on Education, 2024)
The Educational Personnel Training Agency has the responsibility of preparing vocational high school teachers who possess reflective learning skills. Reflective learning involves the practice of engaging in reflective thinking, where individuals delve into their experiences in order to gain fresh insights and appreciations. This study is motivated by the recognition of the importance of Micro Teaching in shaping aspiring vocational high school teachers. To address this concern, it is essential to develop a reflective learning model that is rooted in the Unity of Sciences, which will aid in the preparation of these candidates. The aim of this study is to establish a reflective learning model, grounded in the Unity of Sciences, that will contribute to the growth of professional vocational high school teachers. The research methodology employs a development model design, which encompasses various stages including initial investigation, design, implementation, testing, evaluation, revision, and widespread implementation. The findings of this study indicate that the developed reflective learning model, based on the Unity of Sciences, is valid, practical, and effective in enhancing the competitiveness of vocational high school teacher candidates in the era of digital revolution.